2018
DOI: 10.1007/978-1-4939-7811-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Protocols for Studies of Cross-Seeding Amyloid Assemblies

Abstract: Alzheimer's disease (AD) and type 2 diabetes (T2D) are two common protein aggregation diseases. Compelling evidence has shown a link between AD and T2D, which may derive from interspecies cross-sequence interactions between amyloid-β peptide (Aβ), associated with AD, and human islet amyloid polypeptide (hIAPP), associated with T2D. Herein, we present experimental and computational protocols and tools to study the aggregate structures and kinetics, conformational conversion, and molecular interactions of Aβ-hIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…298 Furthermore, two review articles have focussed on the interactions of IAPP with the membrane 299,300 and another review deals with experimental and computational methods for investigating crossseeding of Aβ and IAPP. 301 These review articles were published and/or submitted in 2018 so that we focus here on the papers published since 2018. A Web of Science search (performed on March 5, 2020) with the keywords "(amylin OR IAPP) AND simulation*" retrieved a total of 71 papers published in the past two years and two months.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…298 Furthermore, two review articles have focussed on the interactions of IAPP with the membrane 299,300 and another review deals with experimental and computational methods for investigating crossseeding of Aβ and IAPP. 301 These review articles were published and/or submitted in 2018 so that we focus here on the papers published since 2018. A Web of Science search (performed on March 5, 2020) with the keywords "(amylin OR IAPP) AND simulation*" retrieved a total of 71 papers published in the past two years and two months.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The molecular dynamics (MD) studies of IAPP have been reviewed recently by Moore et al, and in a broad review article that discusses simulations of several amyloidogenic (poly)­peptides . Furthermore, two review articles have focused on the interactions of IAPP with the membrane , and another review deals with experimental and computational methods for investigating cross-seeding of Aβ and IAPP . These review articles were published and/or submitted in 2018 so that we focus here on the papers published since 2018.…”
Section: High-resolution Structures Of Iappmentioning
confidence: 99%
“…During the last decades, computational studies have been extensively used in the investigation, structural elucidation, and design of amyloid self-assembly, inhibition, and discovery of amyloid materials. , It was recently demonstrated that computational methods can be used for the design of functional amyloid materials binding to other substances (ions or compounds), in a study focusing particularly on cesium ions . Here, we introduced and advanced our recently published approach to design amyloid materials binding to AD drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid β ( Aβ ) peptides associated with AD, consist of 38 to 43 amino acids chains. 2,3 They are products of β - and γ -secretases acting on the transmembrane amyloid precursor protein (APP). 46 Aβ peptides are the main component of extracellular deposits, which are one of the hallmarks of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid β ( Aβ ) peptides associated with AD consist of 38–43 amino acids chains. , They are products of β- and γ-secretases acting on the transmembrane amyloid precursor protein (APP). Aβ peptides are the main component of extracellular deposits, which are one of the hallmarks of AD. , Upon cleavage, Aβ monomers are released into the extracellular environment, where they assemble into oligomers, fibrils, and, eventually, into filaments, that are deposited on and interacting in a complex manner with the neural membranes . These filament-like structures are a major component of amyloid plaques.…”
Section: Introductionmentioning
confidence: 99%